2016
DOI: 10.2134/agronj2015.0485
|View full text |Cite
|
Sign up to set email alerts
|

Organic Supplemental Nitrogen Sources for Field Corn Production after a Hairy Vetch Cover Crop

Abstract: Legume cover crops and organic amendments in combination could meet corn (Zea mays L.) nitrogen (N) needs while optimizing phosphorus (P) inputs. In a 2‐yr field study, we characterized the N‐mineralization dynamics and impacts on corn grain yield of feather meal (FM), poultry litter (PL), pelletized PL (PPL), and a PPL‐FM blend (PFMB) with or without a hairy vetch (Vicia villosa Roth) cover crop. The four amendments, which differed substantially in chemical and laboratory N‐release characteristics, provided c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 52 publications
2
30
2
2
Order By: Relevance
“…Vann et al (2017) and Spargo et al (2016) report similar organic field corn (Zea mays L.) yield when feather meal and pelletized poultry litter were applied at equivalent rates of total N. Similar results were observed by Wild et al (2011) in organic rice (Oryza sativa L.) production. Gaskell (1999) determined that early bell pepper (Capsicum annuum L. var.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Vann et al (2017) and Spargo et al (2016) report similar organic field corn (Zea mays L.) yield when feather meal and pelletized poultry litter were applied at equivalent rates of total N. Similar results were observed by Wild et al (2011) in organic rice (Oryza sativa L.) production. Gaskell (1999) determined that early bell pepper (Capsicum annuum L. var.…”
supporting
confidence: 55%
“…Examples of these practices are the use of herbicides for weed suppression and synthetic suckercides for axillary bud control (Fisher, 2014). Similar approaches to organic research have been used where questions of limited scope were asked and where determination of organic yields under completely organic management was not the goal (Mischler et al, 2010;Spargo et al, 2016).…”
Section: Field Operationsmentioning
confidence: 99%
“…Hairy vetch can supply over 180 kg ha −1 of plant N from the shoots alone, with over 90 kg ha −1 of that being plant available [48,52,58,59]. Previous studies have suggested that a monoculture of hairy vetch can supply the full N requirements of a corn crop on heavier soils that have a long history of manure and legume use [60], which can be attributed to the high N supplying capacity of the soil supplementing the legume-based fertility. Local recommendations are that producers not rely on a cover crop alone to meet corn N demand.…”
Section: Corn Fertility Managementmentioning
confidence: 99%
“…Em resíduos de aveia-preta, o triturador proporciona 43,1% mais cobertura do solo em relação à média dos manejos da cultura com palha dessecada, gradeada ou com rolo faca (Trogello et al, 2013). Desta forma, o efeito da adubação verde foi sinérgico com o da adubação orgânica, vindo de encontro com os resultados obtidos por Spargo et al (2016), que observaram nas produtividades de grãos de milho interação (P < 0,05) entre cultivo anterior de ervilhaca peluda e adubação com cama de aviário em ano com produtividade de 4,6 Mg ha -1 de MVPA, mas não observaram interação entre estes fatores (P > 0,15) em ano que a fabaceae produziu pouco, 1,5 Mg ha -1 de MVPA.…”
Section: Resultados E Discussão A) Produtividades Das Culturasunclassified
“…Acúmulos de P no solo com a aplicação de cama de aviário não foram minimizadas com o cultivo de ervilhaca peluda, e também não afetou (P > 0,05) as produtividades subsequentes de milho doce, porém, não há evidências de interações negativas entre estes dois insumos (ALSUP; KAHN;PAYTON, 2002). Com relação à gestão integrada do N orgânico, aumentos (P < 0,05) nas produtividades de grãos (18,4%), biomassa (22,3%) e absorção de N (68,2%), mas também de nitrato (NO3 -) na profundidade de 0 a 30 cm do solo (50,0%), foram observados com a aplicação de cama de aviário após cultivo de ervilhaca peluda em relação à aplicação do adubo orgânico sem o cultivo anterior da fabaceae (SPARGO et al, 2016).…”
unclassified